Participação do sistema Renina-Angiotensina na Glicose plasmática e na secreção de insulina de Ratos cronicamente tratados com enalapril esubmetidos ao estresse agudo de contenção - Junia Ribeiro de Oliveira Longo Schweizer (2011)
There is increasing evidence of renin-angiotensin system (RAS) involvement in carbohydrate metabolism and its response modulation to stress. Restraint is a straightforward stress model that, although painless, powerfully activates the limbic system, besides activating hypothalamic stress regulator nucleus. This study aimed to evaluate the effects of chronic inhibition of RAS with enalapril upon glucose and insulin levels during acute restraint stress. Male Holtzman rats were treated with enalapril solution 10 mg/kg body weight per day or vehicle for 14 days. A silastic connection was adapted to an atrium catheter. After 1h adaptation, the basal sample was collected and the rats were then submitted to restraint stress. Samples were drawn at 5, 10, 20 and 30min. The experimental groups were divided into: enalapril + restraint (ER), vehicle + restraint (VR) and enalapril + saline (ES). After restraint, there was a hyperglycemic response already at 5min in ER and at 10min VR, with peak at 20 and 10min, respectively (P<0.05). In ES, glucose levels did not vary significantly during the experiment (P>0.05). No significant differences were observed when comparing ER, VR and ES areas under glucose curves (P> 0.05). Restraint induced an important increase in insulin secretion in ER, contrasting with a mild elevation in VR, both with a peak at 20min (P< 0.05). In ES, insulin secretion did not vary significantly (P>0.05). Our data reinforce the response modulation of RAS inhibition to stress and shows, for the first time, that RAS inhibition with enalapril augments the glucose-induced insulin secretion, even in a mild hyperglycemic stress such as in acute restraint.